PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN QUALITY OF WORK LIFE TERHADAP KOMITMEN ORGANISASIONAL PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Surya Wardani; Sari Wulandari; Adrial Falahi; M. Guffar Harahap (Universitas Dharmawangsa, 2023)
This study aims to determine and analyze the influence of leadership style, organizational culture and quality of work life on organizational commitment at the Department of Industry and Commerce, Perbaungan District, Serdang Bedagai Regency. The sampling technique used a total sampling of 70 employees. The data collection method in this study uses primary data. By collecting data through observation and questionnaires (Questionnaire). Based on the results of the t test, it shows that leadership style, organizational culture and quality of work life have a positive and significant effect on organizational commitment. The results of the F test show that leadership style, organizational culture and quality of work life simultaneously or together have a positive and significant impact on organizational commitment. The results of testing the coefficient of determination (R2) obtained an R Square value of 0.843 so that it can be concluded that in this study leadership style, organizational culture and quality of work life contributed to organizational commitment of 84.3% and the remaining 15.7% was influenced by other factors not examined in this research.Keywords: leadership style, organizational culture, quality of work life, organizational commitment